Yi-Shen-Hua-Shi Granule Alleviates Adriamycin-Induced Glomerular Fibrosis by Suppressing the BMP2/Smad Signaling Pathway - Tan, Zhuojing; Si, Yachen; Yu, Yan; Ding, Jiarong; Huang, Linxi; Xu, Ying; Zhang, Hongxia; Lu, Yihan; Wang, Chao; Yu, Bing; Yuan, Li (Frontiers in Pharmacology, 2022)
Focal segmental glomerulosclerosis (FSGS) is a common clinical condition with manifestations of nephrotic syndrome and fibrosis of the glomeruli and interstitium. Yi-Shen-Hua-Shi (YSHS) granule has been shown to have a good effect in alleviating nephrotic syndrome (NS) in clinical and in animal models of FSGS, but whether it can alleviate renal fibrosis in FSGS and its mechanism and targets are not clear. In this study, we explored the anti-fibrotic effect and the targets of the YSHS granule in an adriamycin (ADR)-induced FSGS model and found that the YSHS granule significantly improved the renal function of ADR-induced FSGS model mice and also significantly reduced the deposition of collagen fibers and the expression of mesenchymal cell markers FN, vimentin, and α-SMA in the glomeruli of ADR-induced FSGS mice, suggesting that the YSHS granule inhibited the fibrosis of sclerotic glomeruli. Subsequently, a network pharmacology-based approach was used to identify the potential targets of the YSHS granule for the alleviation of glomerulosclerosis in FSGS, and the results showed that the YSHS granule down-regulated the expressions of BMP2, GSTA1, GATS3, BST1, and S100A9 and up-regulated the expressions of TTR and GATM in ADR-induced FSGS model mice. We also proved that the YSHS granule inhibited the fibrosis in the glomeruli of ADR-induced FSGS model mice through the suppression of the BMP2/Smad signaling pathway.